Financial Strategies and Innovative Behavior in Wine MSMEs: A Causal Model Toward Sustainability in the Valle de Guadalupe - Luna-Andrade, Andrés Antonio; Meraz-Ruiz, Lino; Pérez-Cruz, Omar Alejandro (Journal of the University of Zulia, 2025)
This study proposes a causal model that examines how the perceived effectiveness of financial strategies influences innovative behavior in wine-producing MSMEs in the Valle de Guadalupe one of the leading wine regions in Mexico. The objective is to identify the most effective strategies and assess their impact on both sustainability and competitiveness, with the aim of strengthening these economic units within their dynamic environment. A quantitative methodology was employed, using a correlational-explanatory approach with a non-experimental design. Data were collected through a questionnaire administered to owners, entrepreneurs, directors, managers, and administrators. The results confirmed the proposed hypotheses, showing that organizational culture has a positive influence on innovative behavior. Furthermore, the findings reveal that the perception of financial strategies is directly related to organizational culture and the use of information and communication technologies. In conclusion, most of these enterprises use innovation as a strategic tool for competitiveness, while financial is consolidated as a key element in the adoption of sustainable management practices.